Taming the transplant troll: Exploring racial and ethnic disparities in cytomegalovirus infection among kidney transplant patients. - M Gabriela Cabanilla; Ashlee Dauenhauer; Briana St John; Deirdre Hill; Joshua Larson (PLoS ONE)
Background Cytomegalovirus (CMV) infection poses a significant risk to kidney transplant recipients. This study investigated CMV disease incidence, outcomes, and management challenges in racial and ethnic minority populations following kidney transplantation. Methods This single-center, mixed-methods study included a retrospective cohort analysis of kidney transplant recipients (n = 58) and qualitative surveys of healthcare providers. Patients were categorized as minorities (n = 49) or non-Hispanic whites (n = 9). The primary outcome was CMV disease incidence. Secondary outcomes included graft failure, mortality, and identification of management barriers. Results The cumulative incidence of CMV disease was higher in minorities than in non-Hispanic whites (12.3% vs. 0%, p = 0.58), although the difference was not statistically significant. All graft failures (8.6%, n = 5) occurred in the minority group. Although not statistically significant, all-cause mortality was higher in the minority group (24.5% vs. 11.1%, p = 0.54), with 46.2% of the deaths occurring within 90 days of CMV diagnosis. Qualitative analysis revealed challenges in diagnosis, treatment-related side effects, medication costs, and insurance barriers. The providers emphasized the importance of interdisciplinary collaboration and standardized protocols. Conclusion While limited by the small sample size, this study highlights potential disparities in the incidence and outcomes of CMV disease among minority kidney transplant recipients, suggesting that barriers in care and access may contribute to these differences. These hypothesis-generating findings underscore the need for larger multicenter studies to validate these patterns and to inform targeted strategies that may reduce inequities in post-transplant outcomes.